Mauritius : studies on the social dimensions of globalization - Anker, Richard (ILO GenevaCH, 2001)
Focuses on particular dimensions of globalization, notably the increased and rapid integration of national economies, international trade flows and FDI liberalization and their impact on labour markets. Describes how globalization and social progress in Mauritius have evolved since the early 1980s. Assesses the social impact of globalization, and discusses policy issues.